Pasture enclosures increase soil carbon dioxide flux rate in Semiarid Rangeland, Kenya - Oduor, C.O.; Karanja, N.; Onwong'a, R.; Mureithi, S.; Pelster, David E.; Nyberg, G. (Springer, 2018)
Pasture enclosures play an important role in rehabilitating the degraded soils and vegetation, and may also influence the emission of key greenhouse gasses (GHGs) from the soil. However, no study in East Africa and in Kenya has conducted direct measurements of GHG fluxes following the restoration of degraded communal grazing lands through the establishment of pasture enclosures. A field experiment was conducted in northwestern Kenya to measure the emission of CO2, CH4 and N2O from soil under two pasture restoration systems; grazing dominated enclosure (GDE) and contractual grazing enclosure (CGE), and in the adjacent open grazing rangeland (OGR) as control. Herbaceous vegetation cover, biomass production, and surface (0-10 cm) soil organic carbon (SOC) were also assessed to determine their relationship with the GHG flux rate.Vegetation cover was higher enclosure systems and ranged from 20.7% in OGR to 40.2% in GDE while aboveground biomass increased from 72.0 kg DM ha-1 in OGR to 483.1 and 560.4 kg DM ha-1 in CGE and GDE respectively. The SOC concentration in GDE and CGE increased by an average of 27% relative to OGR and ranged between 4.4 g kg-1 and 6.6 g kg-1. The mean emission rates across the grazing systems were 18.6 μg N m-2 h-1, 50.1 μg C m-2 h-1 and 199.7 mg C m-2 h-1 for N2O, CH4, and CO2, respectively. Soil CO2 emission was considerably higher in GDE and CGE systems than in OGR (P < 0.001). However, non-significantly higher CH4 and N2O emissions were observed in GDE and CGE compared to OGR (P = 0.33 and 0.53 for CH4 and N2O, respectively). Soil moisture exhibited a significant positive relationship with CO2, CH4, and N2O, implying that it is the key factor influencing the flux rate of GHGs in the area.The results demonstrated that the establishment of enclosures in tropical rangelands is a valuable intervention for improving pasture production and restoration of surface soil properties. However, a long-term study is required to evaluate the patterns in annual CO2, N2O, CH4 fluxes from soils and determine the ecosystem carbon balance across the pastoral landscape.